2023
DOI: 10.3390/ani13132095
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Light Spectra on Melatonin Synthesis by the Pineal Gland and Influence on the Immune System in Chickens

Loredana Horodincu,
Carmen Solcan

Abstract: It is well known that the pineal gland in birds influences behavioural and physiological functions, including those of the immune system. The purpose of this research is to examine the endocrine–immune correlations between melatonin and immune system activity. Through a description of the immune–pineal axis, we formulated the objective to determine and describe: the development of the pineal gland; how light influences secretory activity; and how melatonin influences the activity of primary and secondary lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 313 publications
(509 reference statements)
0
3
0
Order By: Relevance
“…Regarding sex hormones; the significant increase in plasma sex hormones concentrations of all treated groups may be attributed to the influence of magnetic applications (MF and MW) on; the reproduction and physiology of birds breeding, alters endocrine and immune systems, [14] and melatonin level in birds. [53] In study by Fernie and Reynolds [14] showed significant changes in the sexual behavioral, courtship, fertility, egg laying, and clutch size of captive kestrels exposed to electro MFs 1 m of a 735-kV for 95 days. The increasing of plasma sex hormones concentration may explain the positive role of MW and MF on improving the laying performance of aged laying quails found herein.…”
Section: Biochemical and Hormonal Parametersmentioning
confidence: 98%
“…Regarding sex hormones; the significant increase in plasma sex hormones concentrations of all treated groups may be attributed to the influence of magnetic applications (MF and MW) on; the reproduction and physiology of birds breeding, alters endocrine and immune systems, [14] and melatonin level in birds. [53] In study by Fernie and Reynolds [14] showed significant changes in the sexual behavioral, courtship, fertility, egg laying, and clutch size of captive kestrels exposed to electro MFs 1 m of a 735-kV for 95 days. The increasing of plasma sex hormones concentration may explain the positive role of MW and MF on improving the laying performance of aged laying quails found herein.…”
Section: Biochemical and Hormonal Parametersmentioning
confidence: 98%
“…Few reports associated the pineal gland with the immune system [22,23] before 1986, when it was shown, for the first time, that MLT could increase antibody production in mice and counteract the immunosuppressive effect of corticosterone and/or restrain stress via an opiatergic mechanism [24][25][26]. These findings were reproduced in different experimental models [27,28], and, in general, the immunoregulatory properties of MLT have been further extended in a variety of animal models and in humans [29][30][31][32][33][34][35][36][37]. Nevertheless, the overall picture of the immunological action of MLT is quite confused.…”
Section: Melatonin and The Immune Systemmentioning
confidence: 98%
“…Nevertheless, the overall picture of the immunological action of MLT is quite confused. Several reports indicate that MLT is a powerful in vivo immunoenhancing factor, suggesting its use as a therapeutic agent whenever it is needed to boost humoral and/or cellular immune responses, while others endow MLT with an anti-inflammatory effect [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. This apparent contradiction might be due to the wide range of concentrations and dosages used, possibly linked to the pleiotropic nature of the molecule or, more probably, to the fact that the immunological consequences of the circadian action exerted by MLT via its specific receptors were seldom discriminated from the other non-circadian effects [ 38 ].…”
Section: Melatonin and The Immune Systemmentioning
confidence: 99%